Tyrosinase positive albinism with familial 46, XY, t(2;4) (q31.2;q31.22) balanced translocation. Issue 7 (July 1991) - Walpole, I R; Mulcahy, M T
Abstract : A subject with clinical and biochemical tyrosinase positive oculocutaneous albinism (OCA) also had a balanced translocation, 46, XY, t(2;4)(q31.2;q31.22). This observation provides evidence for a possible gene locus in the q31 region of chromosome 2 or 4.